The Role of School Based Management and Students’ Academic Performance in Secondary Schools in Owo Local Government Area of Ondo State, Nigeria - Adeolu Joshua Ayeni; Felicia Bosede Bamire (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2022)
The perceived inadequacies in the decentralization of administrative power and authority to the school-based management committee seems to hamper quality education service delivery and is partly responsible for the relatively low level of students’ academic performance in Nigerian public secondary schools. This study therefore examined the key roles performed by the school-based management (SBM) in the aspects of decision-making, physical plant planning, school-community relations, coordination of academic program and policy intervention, as well as implication of these key roles on students’ academic performance in secondary schools in Owo Local Government, Ondo State, Nigeria. The study adopted the descriptive survey research design. Respondents comprised 99 key members of the SBM randomly sampled from nine public secondary schools. Data were collected using School Based Management Questionnaire [SBMQ] and Students’ Academic Performance Inventory [SAPI]. Two research questions and one hypothesis guided the study. Data were analyzed using percentage, mean and multiple regression analysis. The result indicated that the school-based management committee made moderate contributions in all the different dimensions of the key roles that are performed in secondary schools. The result further revealed that a combination of the key roles of SBM jointly accounted for 28.6% (0.286) contribution to students’ academic performance at < 0.05. The study concluded that the School Based Management Committee (SBMC) made a moderate contribution to the school management which accounted for a low contribution to the students’ academic performance; limited contributions of the SBMC were also recorded in the award of school projects, capacity training of teachers and selection of students’ textbooks. It was recommended that the Government through the Ministry of Education should reinvigorate SBM practice and prioritize the significant inputs of the school-based management committee to enhance the quality of decision-making and mobilize adequate resources for infrastructural development and support for teachers’ capacity training to improve the quality of teaching-learning process for better academic performance of students in public secondary schools.